A clinical pharmacological experimental research analysis of the evidence-based rational pharmacotherapeutics of pefloxacin and newer quinolones - Hazra, Moumita (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Pefloxacin is a newer broad-spectrum bactericidal fluoroquinolone antibiotic, with superior antibacterial activity in vivo against pathogenic ocular gram-negative and anaerobic microorganisms and better pharmacokinetic properties. Methods: 100 bacterial conjunctivitis patients were prescribed topical pefloxacin 0.3% ophthalmological drops monotherapy, 2 drops in each eye after every 3 hours for 2 days, and 2 drops in each eye after every 6 hours for next 5 days. The overall recovery of the patients was clinically examined and assessed. The patients who did not recover completely with 0.3% pefloxacin monotherapy ophthalmological drops, were administered topical pefloxacin 0.3% ophthalmological drops, 2 drops in each eye after every 6 hours for the next 3 days, as combination therapy, with other required ophthalmological eye drops, depending on the prognostic follow-up, on days 0, 3, 5, 7, 10, 15, 30, and on further follow-ups. The evidence-based rational pharmacotherapeutic patient percentage topical application requirements of 0.3% pefloxacin ophthalmological drops monotherapy and subsequent combination therapy for complete recovery from bacterial conjunctivitis was thoroughly analysed and assessed. Results: In this study, the patient percentage topical application requirements of pefloxacin 0.3% ophthalmological drops monotherapy and combination therapy in bacterial conjunctivitis patients showed that 93% patients had completely recovered with pefloxacin monotherapy, and 7% patients required pefloxacin combination therapy for complete recovery. The evidence-based rational pharmacotherapeutics of newer quinolones, in global multi-centre tertiary care hospitals, was also well characterized and analytically described. Conclusions: Therefore, 93% patients had completely recovered with the ocular antibiotic pefloxacin 0.3% ophthalmological drops monotherapy, and 7% patients required pefloxacin combination therapy for complete recovery. The evidence-based rational pharmacotherapeutics of newer quinolones was also distinctly delineated.